Monitoring of some dissolved heavy metals in surface waters of north-west Croatia from year 2016 to 2018 - Mlinarić, Patricia (Array, 2020)
Heavy metals have a negative impact on environment and wildlife. In waters, heavy metals appear in two forms, as dissolved and bioavailable; and as solid and non-soluble. We monitored the concentration of dissolved copper, nickel, manganese and iron in water samples at five river locations of north-west Croatia from 2016 to 2018. Concentrations of dissolved nickel measured at Melačka river, near Vularija in Međimurje county and HE Čakovec dam, near Štefanec in Međimurje county were below 5 µg/l and could be considered as not polluted. Concentrations of dissolved copper measured at Plitvica river, near Zbela in Varaždinska county and Horvatska, near Veliko Trgovišće in Krapinsko-Zagorska county were mostly below 5 µg/l and could be considered as not polluted. At Kosteljina river near Jalšje at the Krapinsko-Zagorska county concentrations of dissolved copper were mostly below 5 µg/l; concentrations of dissolved manganese and iron were higher especially during second part of the year, with some fluctuations. For this reason, Kosteljina river could be considered as medium polluted.